Effect of rainfall seasonality on the growth of Cecropia sciadophylla: intra-annual variation in leaf production and node length. (1st July 2013) - Zalamea, Paul-Camilo; Sarmiento, Carolina; Stevenson, Pablo R.; Rodríguez, Manuel; Nicolini, Eric; Heuret, Patrick
Abstract: Patterns of leaf production and leaf fall directly influence leaf area index and forest productivity. Here, we focused on Cecropia sciadophylla individuals inhabiting the extremes of the gradient in seasonality in rainfall at which C. sciadophylla occurs. In Colombia and French Guiana we compared the intra-annual variation in leaf production as well as the intra-annual fluctuation in internode length on a total of 69 saplings ranging in size from 1 to 2 m. The mean rate of leaf production was ~2 leaves mo −1 in both populations, and the rate of leaf production was constant throughout the year. Our results showed monthly variation in internode length and the number of live leaves per sapling in the seasonal habitat and variation only in internode length in the everwet habitat. Because the rate of leaf production is constant at both localities, the difference in number of live leaves per sapling at the seasonal site must reflect seasonal variation in leaf life span. We show that in Cecropia, internode length can serve as an indicator of precipitation seasonality. Finally an open question is whether leaf production in other pioneer species is also independent of climatic seasonal cues. This information could allow us to link growth and climate of secondary forest species and better understand how past and future climate can affect plant growth trajectories.